1821 N.J. Laws 474, An Act to Describe, Apprehend and Punish Disorderly Persons, § 2 - (:unkn) unknown (General Publisher, 1799)
Prohibited the carrying of any pistol, hanger, cutlass, bludgeon, or other offensive weapon, with intent to assault any person.”
--
Keywords: CARRY - INTENT TO COMMIT CRIME